Underrepresentation of women in undergraduate economics degrees in Europe: A comparison with STEM and business - Rigissa Megalokonomou; Marian Vidal-Fernandez; Duygu Yengin (Institute of Labor Economics (IZA), 2021)
In the last decade, the proportion and academic performance of women who pursue university degrees has increased relative to men in a range of developing countries (OECD, 2015). Nonetheless, the percentage of undergraduate economics degrees awarded to women has remained between 30% and 35% during 2001-2018 in the U.S. (Siegfried, 2019). In a recent work by Lundberg and Stearns (2019), they show that the gender gap worsens as women economists progress in their professional careers in the U.S., where they end up representing only 10% of university professors. European countries seem to have less of a "leaky pipeline," where the same figure sits at 22% (Auriol, Friebel, and Wilhelm, 2020). To put this figure into perspective, our paper describes the cross-country underrepresentation of women graduating in economics degrees in Europe relative to their country-specific women/men university graduation rates. Second, we compare the underrepresentation of women in economics to its closest alternative namely business, as well as its gender underrepresented counterpart, STEM (Science, Technology, Engineering, and Mathematics). Finally, we lean on recent evidence to suggest policies to increase the relative share of women pursuing undergraduate economics degrees in Europe with a strong focus on policies aimed at high schools. Overall, we find that, over the period 2013-2018, the underrepresentation of women in economics graduates has worsened in Europe and that on average two of every five students are women. While the gender representation of university graduates in STEM is worse than in economics, it has experienced a mild increase over the period of study. Unlike Economics, its closest alternative, business, has a slight women overrepresentation, with 1.1 women graduating for every man.
Keywords: J16; J24; 330; women; economics; STEM; university